Analysis on Issues of Variable Flow Water System - Jinming Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Variable flow water system has played an important role in the field of energy saving with the Electronic Variable Frequency Drive (VFD) widely used in practical projects. How to control the frequency converter to work properly is an essential issue which we must first emphatically solve. The control technology of frequency converter is closely related to characteristics of pumps. Based on the mathmatical a model of pumps with or without inverters, the article discusses some issues in detail, such as inverters configuration, flow rate regulation and overload. These are key issues of control technology of variable flow water system. For those multiple-pump water systems, the engineers may select synchronous frequency conversion control technology or Add-Sub pumps control technology to achieve the maximum energy-saving benefits. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3294